The problem of autonomous morality - Tugendhat, Ernst (Estudios de Filosofía, 2006)
It can be said, I think, that today we are in a certain disorientation regarding morals, because although almost all of us have quite strong moral convictions, in general we cannot say what they are based on. The reason for this disorientation is that, while before, both in our own culture and in others, morality always had its basis in religion or tradition, such a justification no longer convinces us. Previous Morals were based on an authority that accepted either the authority of God or tradition or both. Consequently, morality had been heteronomous, not autonomous, since it had its foundation in belief and obedience to God or tradition, not in an understanding and a will of its own. The disorientation in which we find ourselves today seems to be rooted in the fact that on the one hand a heteronomous morality no longer convinces us and that, on the other hand, we still do not have a clear understanding of what an autonomous morality is, since contemporary moral conscience is it is made up of a mix of factors from different origins.